2019
DOI: 10.1002/ps.5503
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change and host plant availability on the global distribution of Brontispa longissima (Coleoptera: Chrysomelidae)

Abstract: BACKGROUND The coconut hispine beetle Brontispa longissima Gestro (Coleoptera: Chrysomelidae) is one of the most serious pests of the coconut palm, Cocos nucifera L. (Arecales: Arecaceae) and other palms. The invasion of B. longissima causes major economic and ecological losses worldwide. In this study, the impacts of climate change on the risk of spread were evaluated. CLIMEX was used to project its global potential distribution based on historical climate data (1987–2016) and simulated future climate data (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 37 publications
0
31
0
2
Order By: Relevance
“…Numerous studies have demonstrated the influence that temperature exerts on the development and survival of insects 7,14,39 . Yet, because the response of insects to temperature is species‐specific, studies about the effect of temperature on insect biology are still relevant, particularly for agricultural and forest pests due to their application in pest management and prediction of species distributions under current and projected climate conditions using mechanistic or hybrid models 8,40–42 . In this context, knowledge of the thermal thresholds of insect pests may help in understanding the risks of a given species spreading to regions outside its native range.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the influence that temperature exerts on the development and survival of insects 7,14,39 . Yet, because the response of insects to temperature is species‐specific, studies about the effect of temperature on insect biology are still relevant, particularly for agricultural and forest pests due to their application in pest management and prediction of species distributions under current and projected climate conditions using mechanistic or hybrid models 8,40–42 . In this context, knowledge of the thermal thresholds of insect pests may help in understanding the risks of a given species spreading to regions outside its native range.…”
Section: Discussionmentioning
confidence: 99%
“…(Chen et al 1986, Liao et al 2014); Cassidispa relicta Medvedev is a severe threat to the dominant trees, Betula platyphylla Sukatchiev and Ulmus pumila L., in Inner Mongolian forests in recent years (Liao et al 2018b). Invasive Cassidinae species such as palm-feeding Brontispa longissima (Gestro) and Octodonta nipae (Maulik) are substantial threats to economic crops and native plants (Peng et al 2018, Zou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The historical climate data (1987-2106) were obtained from gridded Climatic Research Unit (CRU) Time-series (TS) version 4.01 over the period 1901-2016, provided on high-resolution (0.5 • latitude, 0.5 • longitude) grids and produced by CRU at the University of East Anglia [21]. Future climate data for 2021-2040, 2041-2060, 2061-2080, and 2081-2100 were obtained based on the methods in Zou et al [22]. For detailed information on future climate data, please refer to Zou et al [22].…”
Section: Climate Datamentioning
confidence: 99%
“…Future climate data for 2021-2040, 2041-2060, 2061-2080, and 2081-2100 were obtained based on the methods in Zou et al [22]. For detailed information on future climate data, please refer to Zou et al [22].…”
Section: Climate Datamentioning
confidence: 99%